Optimal economic growth with recursive preferences: decreasing rate of time preference - Mantel, Rolf R. (1999)
In the field of optimal growth theory, since Ramsey's time it is frequent to maximize a welfare function consisting of the discounted sum of instantaneous utilities, with a constant rate of time preferencie. Such an optimality criterion implies that preferences are independent over time. (Párrafo extraído del texto a modo de resumen)